Improving Mushroom Cultivation Efficiency through Mobile App-based Data Visualization - Hendinata, Laurentius Kevin; Kandinata, Gabriella Christina; Fikri, Ahmad Ilham Rokhul (The Asian Journal of Technology Management (AJTM), 2024)
Abstract. The increasing global population has spurred a greater need for agricultural products, particularly mushrooms, which are valued for their exceptional nutritional content and rapid growth rates. To optimize mushroom cultivation, it's vital to monitor environmental factors like temperature and humidity for ideal growth conditions. This study introduces an Internet of Things (IoT)-based mobile app for ongoing monitoring of temperature and humidity within mushroom cultivation structures, using sensor, microcontroller, LCD display, and mobile apps. The setup involves strategic placement of system components to efficiently gather data. The mobile app boasts a user-friendly interface for easy navigation and access to critical insights. The assessment of data transmission gives efficient information flow, less than 2% missclicks and 96% effectivity score, with minimal delays. Notably, the mobile app's features exhibit high accuracy and efficacy in delivering real-time updates on cultivation conditions. Furthermore, a survey using a Likert scale garnered positive user feedback, affirming the app's potential value in mushroom farming. This innovative system holds promise in elevating sustainability and profitability in the mushroom cultivation sector.  Keywords:  IoT, Monitoring system, Mushroom cultivation, Mobile application